If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3) + 4(x + 1) = 5(x + -1) + x + 3 Reorder the terms: 2(-3 + x) + 4(x + 1) = 5(x + -1) + x + 3 (-3 * 2 + x * 2) + 4(x + 1) = 5(x + -1) + x + 3 (-6 + 2x) + 4(x + 1) = 5(x + -1) + x + 3 Reorder the terms: -6 + 2x + 4(1 + x) = 5(x + -1) + x + 3 -6 + 2x + (1 * 4 + x * 4) = 5(x + -1) + x + 3 -6 + 2x + (4 + 4x) = 5(x + -1) + x + 3 Reorder the terms: -6 + 4 + 2x + 4x = 5(x + -1) + x + 3 Combine like terms: -6 + 4 = -2 -2 + 2x + 4x = 5(x + -1) + x + 3 Combine like terms: 2x + 4x = 6x -2 + 6x = 5(x + -1) + x + 3 Reorder the terms: -2 + 6x = 5(-1 + x) + x + 3 -2 + 6x = (-1 * 5 + x * 5) + x + 3 -2 + 6x = (-5 + 5x) + x + 3 Reorder the terms: -2 + 6x = -5 + 3 + 5x + x Combine like terms: -5 + 3 = -2 -2 + 6x = -2 + 5x + x Combine like terms: 5x + x = 6x -2 + 6x = -2 + 6x Add '2' to each side of the equation. -2 + 2 + 6x = -2 + 2 + 6x Combine like terms: -2 + 2 = 0 0 + 6x = -2 + 2 + 6x 6x = -2 + 2 + 6x Combine like terms: -2 + 2 = 0 6x = 0 + 6x 6x = 6x Add '-6x' to each side of the equation. 6x + -6x = 6x + -6x Combine like terms: 6x + -6x = 0 0 = 6x + -6x Combine like terms: 6x + -6x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| (x^2+3x+5)(4x^2+3)=0 | | -8+15=7 | | 108-3x=6x+12 | | x+12x+11= | | 4/x+2/5+38/45 | | 6n+8=2(n+18) | | 0,2x+0,3=1,3 | | 5n+4=2(n+11) | | 5n+4=2(n+11) | | (0.3+2x)(0.8+2x)=8.53618 | | 4n+13=n-2 | | 10n+2=7(n+2) | | x+16x+48= | | 143-3X=24X+23 | | 2(5x-4)=2(19x+16) | | y-6/6=8 | | 7n+5=5(n+5) | | -1,5x-2=9,5 | | x+12x+20= | | 4(x+5)=38 | | 12-3x=24+x | | 3125+-100x+x^2=0 | | 28x=24 | | -6(2x-1)+3=-12x+9 | | p/3=4 | | 2.5x^2+0.6x=3480 | | x+13x+40= | | 8x-6=8(x+6) | | 9x-2y=0 | | 1/2x+1/4y=12 | | 2(2x+6)=4x+12 | | 3n-2=6-n |